Lensa Gravitasi oleh Lubang Hitam - Premana W Premandi (Institut Teknologi Bandung, 2003)
This is a brief review on the use of gravitational lensing approach to study light propagation near a black hole. Particular attention is payed to the understanding of the caustics to predict the light path. The Schwarzschild black hole is taken as a worked example to show how the perfect alignment images, i.e. Einstein rings, are determined.